Estrutura e diversidade da regeneração lenhosa, invasão biológica e morfometria de Mauritia flexuosa L.f. em veredas no Triângulo Mineiro (MG) - Clemente, Lucas Henrique (2018)
The aims of this work were: to investigate the structure and diversity aspects of woody regeneration in veredas ecosystems (Mauritia flexuosa L.f. palm swamps) and to evaluate the density of invasive species (Chapter I); and to select reproductive individuals of Mauritia flexuosa L.f. through the biometry of fruits and seeds as well as the ecological parameters of the lots collected (Chapter II). The study was conducted from October 2016 to September 2017 in the sub-basins of the Rio Jordão in the municipalities of Araguari and Estrela do Sul and Rio Uberabinha in Uberlândia-MG. For the analysis of the woody community were installed plots of two different dimensions, 4m² (2m x 2m) and 100m² (10m x10m). Total natural regeneration (RNT), diversity (H ') and equability (J') were calculated for the two communities. For the adult individuals of Pinus caribaea Morelet the density values were estimated and the DAP (1.3m), total height (m) and crown area (m²) were measured. Soil coverage was obtained by the linear intercept method. The border areas the sampled fragments were recorded, with values for the minimum radius of native vegetation (RMVN) from each matrix. For each lot of buriti seeds (N = 80 per matrix) the biometric characters and percentages were obtained for predation and fungi incidence. The normality of the data was verified by the Komolgorov-Smirnov test. To detect the differences between the lots was used ANOVA and t test a posteriori. To identify morphometric patterns in allometry of buriti mother trees and fruit and seed characters, principal component analysis (PCA) was performed. A total of 1,407 individuals were sampled, being 891 and 518 individuals in areas I and II, respectively, distributed in 51 species. Melastomataceae (7), Myrtaceae (5), Anacardiaceae (3), Rubiaceae (3) and Aquifoliaceae (2) were the most important families. The alpha diversity (H ') calculated in the veredas was equivalent to 2.70 and 1.75 and equability (J') in 0.78 and 0.72, respectively for areas I and II. Native grasses and woody species were the main categories for soil coverage. Seven buriti reproductive individuals were selected with allometric parameters recorded for total height between 7 and 14.5 m, 4 to 11 m for IMP and AC values between 31.1 and 58.3 m². DAP presented a range of 29.9 to 54.1 cm. There was a significant difference between seed lots (p <0.0001). The largest size for propagule biometry was reported in the municipality of Uberlândia. The levels of predation (> 50%) and incidence of fungi (> 65%) were found in most buriti lots. The DAP and the morphometric characters of the diaspores were the most important variables in the main component analysis (PCA), explaining most of the data variation on the parameters analyzed for M. flexuosa.